2019
DOI: 10.1088/1757-899x/546/4/042042
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method to Enhance O2/N2 Separation on P84 co-polyimide Hollow Fiber Membrane

Abstract: In this study, a simple coating technique to enhance the selectivity performance of P84 co-polyimide hollow fiber polymer membrane was investigated. The hollow fiber membrane was coated with polydimethylsiloxane (PDMS) to prevent gas flow through the defect surface. The prepared membranes were characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM) and pure gas permeation measurement. The pure gas of O2 and N2 were used to determine the permeation prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The first was the evaporation of excess water at 100 °C causing around 5 wt% mass loss in each membrane, while the second was the starting decomposition of P84 co-polyimide that was different in each sample. The pristine membrane started to decompose at a temperature of 531.33 °C, which is consistent with the previously reported data [ 34 , 35 , 43 ]. This indicated the high thermal stability of P84 co-polyimide.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The first was the evaporation of excess water at 100 °C causing around 5 wt% mass loss in each membrane, while the second was the starting decomposition of P84 co-polyimide that was different in each sample. The pristine membrane started to decompose at a temperature of 531.33 °C, which is consistent with the previously reported data [ 34 , 35 , 43 ]. This indicated the high thermal stability of P84 co-polyimide.…”
Section: Resultssupporting
confidence: 92%
“…More detailed methods on ZCC synthesis were described elsewhere [ 29 ]. The hollow fiber membrane was fabricated via dry/wet spinning method with the parameters inspired from Favvas et al [ 34 , 35 ] and Choi et al [ 34 , 35 ] with some adjustments. The P84 co-polyimide and ZCC were dehydrated at 80 °C for 24 h to remove the moisture in advance of membrane preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Then the actual result of the membrane performance was obtained. It is already known that employing low concentration of PDMS could aid the minor defect formation on the membrane surface and result in actual gas separation properties of polymer [5,60]. For CO 2 separation, the neat membrane exhibits CO 2 , N 2 and CH 4 permeability of 4.68, 0.22 and 0.21 barrer, respectively.…”
Section: Single Gas Permeationmentioning
confidence: 99%
“…PDMS is a rubbery material with low selectivity and high permeability that is composed of high flexibility of silane group [62]. Our previous result observed that PDMS has very good compatibility with P84 by forming uniform layer on the membrane surface [5].…”
Section: Single Gas Permeationmentioning
confidence: 99%
See 1 more Smart Citation